Long-term outcomes of patients with chronic HBe-negative infection: Differences and transition between inactive carriers and low viremic carriers. (March 2023) - Rizzo, G.E.M.; Bronte, F.; Rancatore, G.; Graceffa, P.; Falco, G.; Di Marco, V.
Abstract : Background: Chronic HBeAg-negative infection with low viral load levels (< 2000 IU/mL), previously named ''inactive carrier'' (IC), usually has no indication for starting antiviral treatment, but patients with HBeAg-negative chronic infection may be characterize by the presence of viral load between 2, 000-20, 000 IU/mL, called "Low Viremic Carriers" (LVC), which belong to a "grey area". IC have a survival comparable to that of the non-infected general population. LWC have shown low risk of progression to cirrhosis or HCC. Materials and Methods: The aim of our study was to evaluate the natural history of a cohort of HBeAg-negative chronic infection with viral load <20, 000 IU /mL followed up in our tertiary center from 1999 to 2022. Decompensation, HCC development, loss of HBsAg with or without the appearance of anti-HBs and change of virological status (defined as an increase/decrease in HBV-DNA levels compared to the cut-off of 2, 000 IU/ml in at least two consecutive evaluations at 12 and 24 months) were evaluated. Results: We identified 156 patients with HBeAg-negative chronic infection, labeled as chronic carriers. Of them, we identified 106 patients as IC and 40 patients as LCV, showing no statistically significant difference. The long-term follow up (mean 95 ± 162) confirm that the identification of IC status has relevant prognostic implications since these patients are more likely to lose HBsAg (12.3% in IC vs 2.5% in LVC) low incidence (5.6%) of transition from IC to LVC status. Furthermore, 40% of LVC patients transited to IC status and the residual 60% of LVC did not show any negative clinical event. Conclusions: Our data confirm that all HBeAg-negative patients with serum HBV-DNA < 20, 000 IU/mL has a benign natural course even without antiviral therapy. HBsAg loss is unlikely in the group of patients with HBV-DNA levels between 2, 000 IU/mL and 20, 000 IU/mL.